The Efficacy of Topical Cefiderocol Treatment of Experimental Extensively Drug-Resistant Pseudomonas aeruginosa Keratitis Is Dependent upon the State of the Corneal Epithelium - Eric G. Romanowski; Jonathan B. Mandell; Vishal Jhanji; Robert M.Q. Shanks (Antibiotics)
Background: An overlooked factor in the efficacy of topical antibiotics to treat bacterial keratitis is the state of the corneal epithelium. Recently, we evaluated topical cefiderocol for the treatment of extensively drug-resistant (XDR) Pseudomonas aeruginosa (PA) keratitis in eyes with the corneal epithelium abraded. The goal of this study was to use the same model with the corneal epithelium left intact to evaluate the efficacy of cefiderocol and other antibiotics and compare the results to those of the previous study. Methods: NZW rabbit corneas with intact epithelium were inoculated with XDRPA. After 16 h, the rabbits were topically treated with cefiderocol 50 mg/mL, ciprofloxacin 0.3%, tobramycin 14 mg/mL, or saline. Following 8 h of treatment, the corneas were harvested for CFU determinations and cefiderocol concentrations. Results: Only cefiderocol significantly decreased CFU of the XDRPA strain compared with saline. The CFU in the cefiderocol and tobramycin-treated corneas for the XDRPA strain with initially intact epithelium were 1.83–1.4 Log10 greater than those produced in corneas with the abraded epithelium (p < 0.05). Cefiderocol concentrations were 5.02× less in corneas with initially intact epithelium. Conclusions: The efficacy of cefiderocol and tobramycin to treat experimental XDRPA keratitis is dependent on the state of the corneal epithelium.